PENINGKATAN PENGETAHUAN TENTANG PENYALAHGUNAAN DAN PENGGUNASALAHAN OBAT DI KALANGAN PELAJAR SEKOLAH MENENGAH DI YOGYAKARTA - Lestari, Agatha Budi Susiana; Gani, Michael Raharja; Christasani, Putu Dyana (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Drug abuse and misuse among teenagers have been on the rise year after year. These teenagers must have a solid knowledge of drug use. Health education is provided to Yogyakarta high school students in order to improve their understanding of drug abuse and misuse. The health education is being held at SMK Kesehatan Pelita Bangsa Yogyakarta with 92 participants. The activities begin with a pre-test, continue with a presentation about drug abuse and misuse, and conclude with a post-test. Most participants are female (82%) and in the twelfth grade (49%). The average pre-test score of 86.41 increases to 91.41 in the average post-test score, indicating an improvement in respondents' knowledge. The activity hopes to teach students how to use drugs rationally, particularly ones widely abused by teenagers.